PROSES PENGKOTAAN DAN DIVERSIFIKASI LAHAN DI DESA NAMLEA - M Chairul Basrun Umanailo (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2019)
The urbanization process in Namlea village is a consequence of the change in the administrative status of Buru regency into a district. The phenomenon of change affects the social-economic life of the community, such as kinship patterns and interaction patterns that shift from homogeneous to heterogeneous traits. The research location focuses on the village of Namlea in consideration of changes in community structure and the reduction of agricultural land. The number of informers interviewed was as many as farmers, village apparatus, religious figures, community leaders as well as traders. Analytical techniques used to follow the concept of Miles and Huberman where activities in the analysis of qualitative data are conducted interactively and continuously. The results showed that the urbanization process has brought about the impact of changes in the fulfilment of life needs in which life orientation shifts from agriculture to nonagricultural. Diversification is the basis for increasing the value of land selling and the limitation of agricultural products as a result of the increasing number of needs that are not followed by the improvement of land resources and agricultural products.